2022
DOI: 10.32604/cmc.2022.020389
|View full text |Cite
|
Sign up to set email alerts
|

MNN-XSS: Modular Neural Network Based Approach for XSS Attack Detection

Abstract: The rapid growth and uptake of network-based communication technologies have made cybersecurity a significant challenge as the number of cyber-attacks is also increasing. A number of detection systems are used in an attempt to detect known attacks using signatures in network traffic. In recent years, researchers have used different machine learning methods to detect network attacks without relying on those signatures. The methods generally have a high false-positive rate which is not adequate for an industry-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Cross-Site Scripting: Cross-Site Scripting (XSS) [170] is an attack where a malicious actor injects harmful code into a web application or browser, and this code is then executed on the client side [171].The primary objective of this attack is to hijack a user's session by stealing session tokens and cookies [172]- [176].…”
Section: Security Concerns In Web Applications and Browsersmentioning
confidence: 99%
“…Cross-Site Scripting: Cross-Site Scripting (XSS) [170] is an attack where a malicious actor injects harmful code into a web application or browser, and this code is then executed on the client side [171].The primary objective of this attack is to hijack a user's session by stealing session tokens and cookies [172]- [176].…”
Section: Security Concerns In Web Applications and Browsersmentioning
confidence: 99%
“…Table 2 presents a comprehensive overview of the comparison between processing methods across three aspects, with rankings indicating the level of fulfillment for each aspect. The following three aspects were measured in this comparative analysis: [13] String (word) ✓ Doc2Vec [14], SVM [15] Alex et al [16] Static features ✓ DBN [17], Swam algorithm [18] Alqarni et al [19] Static features ✓ Word2Vec [20], LSTM [21] Liang et al [22] Static features ✓ Tree-CNN [23] Shen et al [24] Static features ✓ High-Level Fuzzy Petri Net [25] Alazab et al [26] Static features ✓ SVM He et al [27] Static features ✓ MJDetector Wang et al [28] Static features 1) Flexibility: the given method's ability to capture a wider range of malicious cases. 2) Semantic meaning: the given method's ability to represent the semantic meaning of code.…”
Section: Related Workmentioning
confidence: 99%
“…Alex et al [16] proposed a deep learning-based detection method that utilizes features such as Boolean values, execution time, function calls, break statements, and conditional statements. Alqarni et al [19] particularly targeted JavaScript functions commonly found in malicious code by employing long shortterm memory (LSTM) to capture feature patterns. Similar efforts have utilized deep learning models, such as Tree-CNN [22], high-level fuzzy Petri nets [24], and MJDetector [27].…”
Section: A Feature Engineering-based Approachesmentioning
confidence: 99%
“…Furthermore, their unique configuration, including the open state of the connected sensors, wireless network, and so on, are very vulnerable to technological systems. In recent years, studies have been conducted to investigate cyber security risks to UAVs that are utilized in the military sector [8][9][10][11]. However, little research has been conducted to investigate whether extra cyber hazards exist for the usage of commercially accessible UAVs.…”
Section: Introductionmentioning
confidence: 99%